Waveguide Bragg gratings in Ormocer hybrid polymers - Frey, Lothar; Förthner, Michael; Hellmann, Ralf; Rommel, Matthias; Girschikofsky, Maiko Girschikofsky (Optics Express, 2016)
We report on the fabrication of Bragg gratings within rib-type waveguides of previously UV-cured inorganic-organic Ormocer hybrid polymers by applying the interferometric phase mask technique in conjunction with deep-UV laser radiation. The fabrication process as well as the influence of the applied laser fluence and the length of the Bragg grating on the characteristics of the Bragg grating's transmission and reflection spectra are discussed and compared to numerical simulations and calculations. Depending on the applied laser fluence and the chosen grating length, waveguide Bragg gratings with strong reflectivities of up to 98% and narrow bandwidths of down to 120 pm have been achieved. (C) 2016 Optical Society of America